2023
DOI: 10.1155/2023/9477442
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Treatment Protocols in the Efficacy and Safety of Anti‐EGFR Medicines in Combination with Standard Therapy for Patients with Nasopharyngeal Cancer: A Meta‐Analysis

Abstract: Objective. This study was conducted to compare the efficacy of standard therapy (radiotherapy/RT/CT) with that of antiepidermal growth factor receptor (anti-EGFR) monoclonal antibody (NPC) therapy in patients with advanced nasopharyngeal cancer. Methods. A meta-analysis was performed to meet the objective of this study. The English databases PubMed, Cochrane Library, and Web of Science were searched. The literature review compared anti-EGFR-targeted therapy with conventional therapy practices. The main outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%